Nonconventional optical systems using varifocal lenses - Ojeda Castaneda, Jorge; Gómez-Sarabia, Cristina Margarita (Photonics Letters of Poland, 2015)
We discuss the first order design of four optical devices, which use varifocal lenses for implementing the following optical systems: a single-lens zoom system, a two-lens afocal system with tunable angular magnification, a three-lens telephoto objective with extremely low, tunable telephoto ratio (which does not require any axial displacement between its composing elements) and a telephoto objective that has zero Petzval sum. Full Text: PDF References I. Kitajima, "Improvement in lenses", British Patent 250, 268 (July 29, 1926). DirectLink W.T. Plummer, J.G. Baker, J. van Tassell, "Photographic optical systems with nonrotational aspheric surfaces", Appl. Opt. 38, 3572 (1999). CrossRef W. T. Plummer, "Unusual optics of the Polaroid SX-70 Land camera", Appl. Optics 21, 196 (1982). CrossRef A.W. Lohmann, "Improvements relating to lenses and to variable optical lens systems formed for such a lenses", British Patent 998, 191 (May 29, 1964). A.W. Lohmann, Republic Française 1, 398, 351 (June 10, 1964). A.W. Lohmann, Italy Patent 727, 848 (June 19, 1964). A. W Lohmann, "A New Class of Varifocal Lenses", Appl. Opt. 9, 1669 (1970). CrossRef L. W. Alvarez, "Two-element variable-power spherical lens", U.S. patent 3,305,294 (21 February 1967). DirectLink L. W. Alvarez and W. E. Humphrey, "Variable-power lens and system", U.S. patent 3,507,565 (21 April 1970). DirectLink L. W. Alvarez, "Development of variable focus lenses and a new refractor", J. Am. Optometric Assoc. 49, 24 (1978). DirectLink A. Lohmann and D. P. Paris, "Variable Fresnel Zone Pattern", Appl. Opt. 6, 1567 (1967). CrossRef G. L. Rogers and L. C. G. Rogers, "The Interrelations between Moiré Patterns, Contour Fringes, Optical Surfaces and Their Sum and Difference Effects", Opt. Acta 24, 15 (1977). CrossRef J. M. Burch and D. C. Williams, "Varifocal moiré zone plates for straightness measurement", Appl. Opt. 16, 2445 (1977). CrossRef A. Kołodziejczyk and Z. Jaroszewicz, "Diffractive elements of variable optical power and high diffraction efficiency", Appl. Opt. 32, 4317 (1993). CrossRef H. W. Ren, Y. H. Fan, S. Gauza, and S. T. Wu, "Tunable-focus flat liquid crystal spherical lens", Appl. Phys. Lett. 84, 4789–4791 (2004). CrossRef Stephan Reichelt and Hans Zappe, "Design of spherically corrected, achromatic variable-focus liquid lenses", Opt. Express 15, 14146 (2007). CrossRef Alexandre Mermillod-Blondin, Euan McLeod, and Craig B. Arnold, "High-speed varifocal imaging with a tunable acoustic gradient index of refraction lens", Opt. Lett. 33, 2146 (2008). CrossRef Martí Duocastella, Giuseppe Vicidomini, and Alberto Diaspro, "Simultaneous multiplane confocal microscopy using acoustic tunable lenses", Opt. Exp. 22, 19293 (2014). CrossRef J. Ojeda-Casta-eda, Cristina M. Gómez-Sarabia, Sergio Ledesma, "Tunable focalizers: axicons, lenses, and axilenses", SPIE Proc. 8833, 883306 (2013). CrossRef Jorge Ojeda-Castaneda, Sergio Ledesma and Cristina M. Gómez-Sarabia, "Tunable apodizers and tunable focalizers using helical pairs", Photonics Letters of Poland 5, 20 (2013). CrossRef Jim Schwiegerling and Carmen Paleta-Toxqui, "Minimal movement zoom lens", Appl. Opt. 48, 1932, (2009). CrossRef J.-H. Sun, B.-R. Hsueh, Y.-C. Fang, J. MacDonald, and C.-C. Hu, "Optical design and multiobjective optimization of miniature zoom optics with liquid lens element", Appl. Opt. 48, 1741–1757 (2009). CrossRef Jorge Ojeda-Castaneda, Cristina M Gómez-Sarabia and Sergio Ledesma, "Novel zoom systems using a vortex pair", Asian Journal of Physics 23, 415 (2014). DirectLink Jorge Ojeda-Castaneda, Cristiana M. Gómez-Sarabia and Sergio Ledesma, "Compact telephoto objectives with zero Petzval sum using varifocal lenses", Asian Journal of Physics 23, 535 (2014). DirectLink P. Mouroulis and J. Macdonald, Geometrical Optics and Optical Design, (New York, Oxford University Press, 1997). A. Cox, A system of Optical Design (London, Focal Press, 1967).